Distribution and Structure of Purkinje Fibers in the Heart of Ostrich (Struthio camelus) with the Special References on the Ultrastructure - Paria Parto; Mina Tadjalli; S. Reza Ghazi; Mohammad Ali Salamat (International Journal of Zoology)
Purkinje fibers or Purkinje cardiomyocytes are part of the whole complex of the cardiac conduction system, which is today classified as specific heart muscle tissue responsible for the generation of the heart impulses. From the point of view of their distribution, structure and ultrastructural composition of the cardiac conduction system in the ostrich heart were studied by light and electron microscopy. These cells were distributed in cardiac conducting system including SA node, AV node, His bundle and branches as well as endocardium, pericardium, myocardium around the coronary arteries, moderator bands, white fibrous sheet in right atrium, and left septal attachment of AV valve. The great part of the Purkinje fiber is composed of clear, structure less sarcoplasm, and the myofibrils tend to be confined to a thin ring around the periphery of the cells. They have one or more large nuclei centrally located within the fiber. Ultrastructurally, they are easily distinguished. The main distinction feature is the lack of electron density and having a light appearance, due to the absence of organized myofibrils. P-cells usually have two nuclei with a mass of short, delicate microfilaments scattered randomly in the cytoplasm; they contain short sarcomeres and myofibrillar insertion plaque. They do not have T-tubules.